The weapons that changed the world - Hogg, Ian V. (Ebury Press, 1986)
The Weapons That Changed The World' tells the dramatic story of the development of key armaments -- the key weapons of modern history, from 1860 to the 1980s -- in technological, strategic, tactical and historical terms. Covering land, sea and air warfare, it explains what these weapons were, how they developed and the impact they had on the battlefield, for with the birth of modern industry and the growth of nationalism in the nineteenth century, the whole nature of warfare was revolutionized. Fully illustrated throughout with explanatory artwork -- including specially developed illustrations to demonstrate the significance of a specific weapon in action -- and photographs, The weapons that changed the world not only gives you an invaluable insight into the great military events of the immediate past. It also brings to vivid life the dramatic events which have shaped the world of today.